THEORETICAL PRINCIPLES FOR PROVISION OF OPTIMUM ELECTRIC POWER LOSS RATES IN POWER SYSTEM NETWORKS - M. I. Fursanov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper shows how it is possible to determine direction (motion path) of optimum power state on the basis of analysis of power transmission cost dependences in the function of relative load losses in the network. Quantitative criteria making possible to move purposefully in the zone of economically justified loss rates are proposed in the paper. Structural algorithm for determination of optimum values of discrete parameters of networks that make actual electric power loss rates very close to optimum ones have been developed and realized.